SOX4 is essential for prostate tumorigenesis initiated by PTEN ablation - Bilir, Birdal (Cancer Res, 2015)
Understanding remains incomplete of the mechanisms underlying initiation and progression of prostate cancer, the most commonly diagnosed cancer in American men. The transcription factor SOX4 is overexpressed in many human cancers, including prostate cancer, suggesting it may participate in prostate tumorigenesis. In this study, we investigated this possibility by genetically deleting Sox4 in a mouse model of prostate cancer initiated by loss of the tumor suppressor Pten. We found that specific homozygous deletion of Sox4 in the adult prostate epithelium strongly inhibited tumor progression initiated by homozygous loss of Pten. Mechanistically, Sox4 ablation reduced activation of AKT and β-catenin, leading to an attenuated invasive phenotype. Furthermore, SOX4 expression was induced by Pten loss as a result of the activation of PI3K-AKT-mTOR signaling, suggesting a positive feedback loop between SOX4 and PI3K-AKT-mTOR activity. Collectively, our findings establish that SOX4 is a critical component of the PTEN-PI3K-AKT pathway in prostate cancer, with potential implications for combination targeted therapies against both primary and advanced prostate cancers.